1987
DOI: 10.1016/0014-5793(87)81021-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin inhibits VIP‐ and isoproterenol‐stimulated cyclic AMP accumulation in rat prostatic epithelial cells

Abstract: The dual regulation of cyclic AMP accumulation was studied in rat prostatic epithelial cells incubated with somatostatin, vasoactive intestinal peptide (VIP), and the fl-adrenergic agent isoproterenol. Somatostatin noncompetitively inhibited the stimulatory effect of VIP and isoproterenol, but it did not alter basal cyclic AMP levels. In addition to the multifactorial regulation of the cyclic AMP system in rat prostatic epithelium, these results suggest that somatostatin may play a physiological role at this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The presence of these subepithelial nerves in the ampular acini suggests a role for the VIP in the regulation of their secretory activity (Juarranz et al, 2001; Ventura et al, 2002). This agrees with the detection of vipergic receptors in the epithelium of rat prostate (Carmena et al, 1985; Carmena et al, 1986a; Carmena et al, 1986b; Carmena et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…The presence of these subepithelial nerves in the ampular acini suggests a role for the VIP in the regulation of their secretory activity (Juarranz et al, 2001; Ventura et al, 2002). This agrees with the detection of vipergic receptors in the epithelium of rat prostate (Carmena et al, 1985; Carmena et al, 1986a; Carmena et al, 1986b; Carmena et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…The mechanisms by which ArSS1 causes muscle contraction in A. rubens are unknown. One possibility would be that it inhibits the release of a muscle relaxant, as has been reported for SS ( 41 , 42 ). Alternatively, ArSS1 may have a direct excitatory effect on muscle in starfish.…”
Section: Discussionmentioning
confidence: 94%
“…However, the myoexcitatory effect of ArSS1 in A. rubens is interesting because hitherto it has been discovered that SS-type and ASTC-type neuropeptides in other taxa typically act as inhibitory regulators of physiological processes at the cellular level ( 13 , 14 , 23 26 ). There are reports of SS causing muscle contraction of guinea pig gastric smooth muscle cells, but investigation of the mechanisms of action indicate that this is a consequence of SS causing inhibition of the release of a muscle relaxant (e.g., vasoactive intestinal peptide) [i.e., SS is causing disinhibition ( 41 , 42 )]. The mechanisms by which ArSS1 causes muscle contraction in A. rubens are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The precise physiological functions of ␤-adrenergic receptors in the prostate gland remain speculative, but it has been suggested that a tight coupling between androgen receptor and ␤-adrenergic receptor pathways may be a prerequisite for functional differentiation at that level [18]. As expected, ␤-adrenergic agonists stimulate adenylate cyclase activity in this reproductive organ [19,20]. However, the behavior of this crucial step in the ␤-adrenergic signal-transduction system in the diabetic prostate remains unknown.…”
Section: Introductionmentioning
confidence: 89%